2013
DOI: 10.1007/s00220-013-1844-5
|View full text |Cite
|
Sign up to set email alerts
|

The Anomaly Line Bundle of the Self-Dual Field Theory

Abstract: In this work, we determine explicitly the anomaly line bundle of the abelian self-dual field theory over the space of metrics modulo diffeomorphisms, including its torsion part. Inspired by the work of Belov and Moore, we propose a non-covariant action principle for a pair of Euclidean self-dual fields on a generic oriented Riemannian manifold. The corresponding path integral allows one to study the global properties of the partition function over the space of metrics modulo diffeomorphisms. We show that the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(77 citation statements)
references
References 37 publications
(290 reference statements)
1
76
0
Order By: Relevance
“…In [3] (with some refined arguments presented in Appendix A), we showed that the anomaly line bundle A of the self-dual field theory is given by…”
Section: The Anomaly Line Bundlementioning
confidence: 96%
See 2 more Smart Citations
“…In [3] (with some refined arguments presented in Appendix A), we showed that the anomaly line bundle A of the self-dual field theory is given by…”
Section: The Anomaly Line Bundlementioning
confidence: 96%
“…While the global gravitational anomalies of chiral fermionic field theories were understood a long time ago [1], a formula for the global anomaly of the self-dual field theory on generic manifolds was derived only recently [3,4]. A self-dual 2ℓ-form field on a 4ℓ`2-dimensional manifold can be naturally sourced by a 2ℓ`1-form abelian gauge field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A formula for the global anomaly of the self-dual field was determined in [1], but only in the case when the self-dual field has no zero modes, or equivalently when the middle-degree cohomology of the underlying manifold vanishes. A general formula for the gravitational anomaly was determined in [5], building on [6,27]. The formula below, which includes the coupling to a background abelian gauge field, was proven in [7].…”
Section: Self-dual 2-formmentioning
confidence: 99%
“…Previous checks of global anomaly cancellation in dimension higher than 2 include type I supergravity [1,2], 11-dimensional supergravity [3,4] and type IIB supergravity [5]. In the present paper, we use recent results concerning the global gravitational anomaly of the self-dual field [6,5,7] in order to check the cancellation of global mixed gaugegravitational anomalies in M-theory backgrounds containing M5-branes. The cancellation of local gravitational anomalies in such backgrounds was checked in [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%